2022
DOI: 10.3390/plants11202729
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein Profile of Rice (Oryza sativa L.) Seedlings under Osmotic Stress after Pretreatment with Chitosan

Abstract: This study aims to identify novel chitosan (CTS)-responsive phosphoproteins in Leung Pratew 123 (LPT123) and Khao Dawk Mali 105 (KDML105) as drought-sensitive rice cultivars and differences in the CTS response. Rice seeds were soaked in CTS solution before germination, and 2- and 4-week-old rice seedlings sprayed with CTS before osmotic stress comprised the following four groups: (1) seedlings treated with distilled water; (2) seedlings treated with CTS; (3) seedlings pretreated with distilled water and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Browning of the root tip also indirectly indicates the accumulation of phenolic compounds, as mentioned by many researchers [29,39,64,68]. The reduction in plant growth rate upon application of the chitosan is further corroborated by our study on cv.…”
Section: Discussionsupporting
confidence: 88%
“…Browning of the root tip also indirectly indicates the accumulation of phenolic compounds, as mentioned by many researchers [29,39,64,68]. The reduction in plant growth rate upon application of the chitosan is further corroborated by our study on cv.…”
Section: Discussionsupporting
confidence: 88%
“…However, the application of the FN13, FCN13, and FON13 bioformulations did not affect proline accumulation in rice plants under normal conditions. Previous studies reported drought-induced proline accumulation in rice leaves ( Xiong et al , 2012 ; Dien et al , 2019 ; Pongprayoon et al , 2022 ).…”
Section: Resultsmentioning
confidence: 94%
“…Chitosan and its derivatives have been employed as bioactive chemicals or binding materials in mixtures with other substances to promote plant growth and development ( Stasińska-Jakubas and Hawrylak-Nowak, 2022 ) and secure protection against plant pathogens ( Stanley-Raja et al , 2021 ). The involvement of chitosan in plant defense responses to biotic and biotic stresses have been reported in several plants, such as grapes ( Vitis vinifera L.) ( Singh et al , 2019 ) and rice ( O. sativa L.) ( Stanley-Raja et al , 2021 ; Pongprayoon et al , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation